Chemo-enzymatic functionalized sustainable cellulosic membranes: Impact of regional selectivity on ions capture and antifouling behavior. (15th February 2022) - Asad, Mohammad; Asiri, Abdullah M.; Azum, Naved; Monti, Susanna; Karim, Zoheb
Abstract: Most of the polymeric membranes synthesized for decentralization of polluted water use fossil-based components. Thus, there is an urgent need to create robust and tunable nano/micro materials for confidently designing efficient and selective polymeric water filters with guaranteed sustainability. We have chosen a robust high-grade microfibrillated cellulose (MFC) as the functional material and selectively tuned it via enzymatic catalysis, which led to the attachment of phosphate group at the C6 position, followed by esterification (fatty acid attachment at C2 and C3 carbon), which led to the increase in its antifouling properties. We have demonstrated the robustness of the functionalization by measuring the separation of various metal ions, and the antifouling properties by adding foulants, such as Bovine Serum Albumin (BSA) and cancerous cells to the test solutions. These prototype affinity MFC membranes represent the most promising type of next-generation high-performance filtration devices for a more sustainable society. Graphical abstract: Unlabelled Image